Family Therapy in Family Medicine (Portuguese Journal of Family Medicine and General Practice, 2007)
The author proposes a model of clinical intervention in general practice leading to a systemic therapeutic plan. Selects and describes how to use the major tools 'Systems Thinking' and 'Family Interview', common to both Family Therapy.
Keywords: Family; Family Interview; Family Therapy